Antibacterial effects of ofloxacin, clindamycin and sultamicillin on surgical removal of impacted third molars. - (:unkn) unknown (My University, 1992)
This study examined the bacteraemia following surgical removal of impacted mandibular third molars and evaluated the antibacterial effects of Ofloxacin, Clindamycin, Sultamicillin, used as prophylactic medications. The study involved a hundred healthy patients whose mandibular third molars were impacted horizontally. These patients were divided into four groups each including 25 individuals. One of the four groups was the control group. The other groups were those to which Ofloxacin, Clindamycin, and Sultamicillin were administered one hour before the operation and in the following 4 days postoperatively. Blood samples were taken before and immediately after the operation, and then, 1 and 24 hours postoperatively. Following the incubation of the samples under aerobic and anaerobic conditions, the samples were examined microbiologically. Preoperative samples were found to be negative. In the immediate postoperative samples, bacteraemia was found in 44% of the control group, 40% of Ofloxacin and Clindamycin groups and 36% of the Sultamicillin group. In the samples taken 1 hour after the operation, bacteraemia was found in 28% of the control group, 20% of the Ofloxacin group and 24% of the Clindamycin and Sultamicillin groups. In the control group, only 2 cases showed positive culture in the blood samples taken 24 hours after the operation. In conclusion, the antibiotics, Ofloxacin, Clindamycin, Sultamicillin have a significant effect in decreasing the risk of postoperative infection and bacteraemia.